2011
DOI: 10.2147/opth.s23772
|View full text |Cite
|
Sign up to set email alerts
|

Basic training module for vitreoretinal surgery and the Casey Eye Institute Vitrectomy Indices Tool for Skills Assessment

Abstract: BackgroundThe purpose of this study was to design and implement a vitreoretinal training module that would be useful for ophthalmology residents and fellows to learn the basic maneuvers required in vitreoretinal surgery.MethodsA prospective pilot study evaluating the training module was undertaken in 13 ophthalmology trainees (residents and vitreoretinal fellows) with varying levels of vitreoretinal training experience. A vitreoretinal training module was designed and consisted of a three-port vitrectomy setup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 15 publications
(8 reference statements)
0
22
0
Order By: Relevance
“…The model was shown to discriminate between experienced and inexperienced surgeons in terms of operating time and the success rate of membrane peeling (relations to other variables) [ 113 ]. This was similarly tested in a study by Yeh et al where, using the artificial VitRet Eye Model (Phillips Studio, Bristol, UK) filled with vitreous-like fluid to simulate a variety of vitreoretinal surgery procedures, a positive correlation was observed between the trainees’ level of experience and total score [ 114 ]. In terms of effectiveness, the models by Yeh and Hirata showed internal acceptability and contained effects, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The model was shown to discriminate between experienced and inexperienced surgeons in terms of operating time and the success rate of membrane peeling (relations to other variables) [ 113 ]. This was similarly tested in a study by Yeh et al where, using the artificial VitRet Eye Model (Phillips Studio, Bristol, UK) filled with vitreous-like fluid to simulate a variety of vitreoretinal surgery procedures, a positive correlation was observed between the trainees’ level of experience and total score [ 114 ]. In terms of effectiveness, the models by Yeh and Hirata showed internal acceptability and contained effects, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The highest scoring domains on the MERSQI instrument were type of data and data analysis in which only Yeh et al [21] did not achieve maximum points, given that their data were non-objective and descriptively analyzed only. Lowest scoring domain was the validity of evaluation instrument.…”
Section: Resultsmentioning
confidence: 99%
“…Lowest scoring domain was the validity of evaluation instrument. Thomsen et al [22] was the only to fulfill the criterion for reporting internal structure by testing internal consistency across all modules with Cronbach’s α. Jonas et al, [23] Vergmann et al, [24] and Thomsen et al [22] adequately reported content and five studies (Rossi et al, [25] Solverson et al, [26] Yeh et al, [21] Vergmann et al, [24] and Thomsen et al [22]) reported relationships with other variables. Grodin et al [27] did not score any points in validity of evaluation instrument.…”
Section: Resultsmentioning
confidence: 99%
“…Quality surgical skill teaching is an important aspect of the resident training program, because the pattern of ocular injuries in pediatric and adult population may vary from simple to grievous injuries. [123456] In routine training programs, theoretical and examination skills are often dealt in detail; however, acquisition of finer surgical skills is often a tough task and it can only be obtained through continuous practice. There are reports in the literature which have evaluated the effect of surgical training on artificial eyes/goat's eye and other models for mainly cataract surgery skills’ enhancement.…”
mentioning
confidence: 99%
“…Similarly, few other studies have evaluated the vitreoretinal surgical skill enhancement. [2345] In literature, there is a clear lack of surgical skill enhancement techniques under complex circumstances like traumatic globe injuries. In addition, the major limitation of these techniques is the lack of real tissue experience, which indeed is the most important aspect in enhancing the microscopic surgical skills.…”
mentioning
confidence: 99%